Bulletin No. 41. The Precambrian Geology and Geochronology of Minnesota - Goldich, Samuel S.; Nier, Alfred O.; Baadsgaard, Halfdan; Hoffman, John H.; Krueger, Harold W. (Minnesota Geological Survey, 1961)
Five map inserts as pdfs, scales from 1:15,000 to 1:2,500,000. This bulletin is an outstanding example of the cooperation of several scientists and scientific organizations. Without the cooperation of all concerned, such a comprehensive correlation of age determinations and regional geology would have been impossible short of many years of work. The results are a particularly important demonstration of cooperation among geologists, chemists, and physicists. Radioactivity dating of a large number of igneous and metamorphic rocks by the potassium-argon and the rubidium-strontium methods is the basis for revision of the classification of the Precambrian rocks of Minnesota. The major divisions of the three-fold classification are made at time boundaries of 2.5 and 1.7 billion years (b.y.), corresponding to the time of two major orogenies, the Algoman and the Penokean, respectively. The eras are referred to as Early, Middle, and Late Precambrian in preference to the older terminology of Earlier, Medial, and Later Precambrian. The division between the Early and Middle Precambrian is placed at the time of the Algoman rather than of the older Laurentian orogeny. The division between the Middle and Late Precambrian is made on the basis of the Penokean orogeny which resulted in a mountain chain that extended from central Minnesota through Wisconsin into Michigan. The Penokean Mountains formerly were assigned erroneously to late Keweenawan time. The Early Precambrian rocks are divided into the Ontarian and the Timiskamian systems. The Ontarian rocks include the Keewatin group of Minnesota and the Coutchiching metasediments which underlie the Keewatin greenstones in Ontario. Some of the gneisses in the Giants Range and the Vermilion granite regions of Minnesota probably were derived by metamorphism of ancient sediments that were deposited prior to the great outpouring of basalt flows assigned to the Ely greenstone of the Keewatin group.